Padrões da riqueza de espécies de insetos galhadores em áreas florestais e jardins ornamentais da Serra de Baturité-Ceará: uma reflexões para pensar a proteção à biodiversidade em uma área protegida sob pressão - Feitosa, Gabriela Xavier Franco (2025)
The creation of Conservation Units (CUs) is one of the most widely used strategies for ecosystem protection. However, in some cases, they may not be effective in achieving the objective of protecting biodiversity, as anthropogenic pressures reduce biodiversity even within the boundaries of protected areas. Conservation goals will only be truly achieved if CUs successfully safeguard biodiversity, thus ensuring its perpetuation. Insects are important environmental indicators because they are part of a diverse faunal group. Gall-forming insects are highly specialized herbivores that induce gall formation in plant tissues, maintaining close and specific relationships with their host plants. This high specificity makes them sensitive bioindicators of environmental integrity and the presence of native vegetation. Changes in vegetation cover, such as the replacement of native species with exotic plants in ornamental gardens. This research aimed to assess how much of the native biodiversity of galling insects can be maintained in ornamental gardens in one of the most important forests for conservation in Ceará: the Serra de Baturité forest. The research was conducted through field collections between April and July 2024, in the municipalities of Guaramiranga and Pacoti. Forty-eight collection points were established at the Hotel Vale das Nuvens, Chalé Nosso Sítio, UECE Campus, and Revis Periquito Cara-suja. Collections lasted 40 minutes at each observation point and covered three types of environments: ornamental gardens, secondary areas, and preserved areas. We compared the richness and incidence of galls among these three environments, verifying differences in gall quantity and richness between the gardens and preserved and secondary forests. To this end, the ANOVA test was applied to analyze whether there were differences in gall richness and occurrence between environments, using the R software. Seventy-nine gall morphotypes were found on 19 plant species belonging to 15 botanical families. Six distinct gall morphologies were also recorded: globoid, fusiform, conical, cylindrical, lenticular, and rolled margin. These structures occurred on leaves, stems, buds, and veins, with colors ranging from green, brown, pink, and yellow. Gall richness was mainly concentrated in secondary forests on the UECE Campus and the Vale das Nuvens Hotel, as well as in the preserved areas of the Vale das Nuvens Hotel and Revis. A total of 1,099 galls were collected, with the families Piperaceae (N=201) and Melastomataceae (N=75) standing out as the most abundant. Ornamental gardens, on the other hand, had a significantly lower incidence and richness of galls, revealing the limitations of ornamental gardens. These data indicate that anthropized areas, as long as they maintain native vegetation, can still support a rich diversity of galling insects, but that gardens cultivated without native flora harbor fewer species than would be possible if the landscaping incorporated more of the local biodiversity.